2006
DOI: 10.1038/nature05273
|View full text |Cite
|
Sign up to set email alerts
|

Self-cooling of a micromirror by radiation pressure

Abstract: Cooling of mechanical resonators is currently a popular topic in many fields of physics including ultra-high precision measurements, detection of gravitational waves and the study of the transition between classical and quantum behaviour of a mechanical system. Here we report the observation of self-cooling of a micromirror by radiation pressure inside a high-finesse optical cavity. In essence, changes in intensity in a detuned cavity, as caused by the thermal vibration of the mirror, provide the mechanism for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
954
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 936 publications
(968 citation statements)
references
References 30 publications
11
954
1
2
Order By: Relevance
“…This dependence is known as the optical spring effect from the linear variation of optical force with the device's position. In contrast to conventional cavity optomechanics in which the optical spring vanishes when the detuning is zero [26][27][28] , our result shows a maximal negative frequency shift near zero detuning, indicating the strongest negative optical spring. This distinction is because the optical force in our system is generated by the evanescent field outside the cavity, instead of the intra-cavity field.…”
Section: Resultscontrasting
confidence: 89%
“…This dependence is known as the optical spring effect from the linear variation of optical force with the device's position. In contrast to conventional cavity optomechanics in which the optical spring vanishes when the detuning is zero [26][27][28] , our result shows a maximal negative frequency shift near zero detuning, indicating the strongest negative optical spring. This distinction is because the optical force in our system is generated by the evanescent field outside the cavity, instead of the intra-cavity field.…”
Section: Resultscontrasting
confidence: 89%
“…Finally, we discuss how the average phonon occupancy can be retrieved from the spectrum of the optical cavity output. We note that these results can be applied to a wide range of experimental realizations of cavity self-cooling [9,11,12].…”
mentioning
confidence: 83%
“…Finally, we discuss how the average phonon occupancy can be retrieved from the spectrum of the optical cavity output. We note that these results can be applied to a wide range of experimental realizations of cavity self-cooling [9,11,12].We treat the laser driven optical cavity mode coupled to the mechanical resonator mode as an open quantum system and adopt a rotating frame at the laser frequency ω L . The system Hamiltonian is given by [16,17] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, extensive studies have been conducted during the last decade on how to cool down the effective temperature of the mirror [3,4,5,6,7]. Recently, studies on cavity optomechanical systems have found a wide range of applications such as quadrature squeezing of polariton [8], generation of Kerr nonlinearity [9], and distant state entanglement [10,11].…”
Section: Introductionmentioning
confidence: 99%